Peran dan Tanggung Jawab Guru dalam Menanamkan Nilai Agama dan Nilai Moral pada Anak Usia Dini di Lembaga PAUD - Yusri, Dairina; Mandailing, Elfa Marlina; Hasibuan, Sahnauli; Marhani, Marhani (Prodi PIAUD STAI Sumatera Medan, 2021)
This paper was written with the aim of describing the roles and responsibilities of teachers in instilling religious and moral values ​​in early childhood in PAUD institutions. The method used in the implementation of this research is descriptive qualitative with aapproach library research (library study). The results of the study show that the roles and responsibilities of teachers based on the variables studied are carried out well, there are several appropriate and effective methods for AUD as a stimulus for inculcating religious and moral values ​​including exemplary methods, habituation, advice and punishment. But in the process, it does not run smoothly, there are obstacles (factors) that affect the family, community, and school environment itself. Departing from this so that it can be achieved as expected requires involvement and cooperation between these factors.